Rutinitas Kerja Jurnalis Media Online Dalam Pikiran Rakyat Media Network - ,, Yuliawati; Kurniawati, Nia Kania; Yusanto, Yoki; Srilestari, Eka Elviani (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
This study discusses the routine of journalists in producing news in online media that is based on the Pikiran Rakyat Media Network, namely Serangnews.pikiran-rakyat.com and Kabarbanten.pikiran-rakyat.com. the research is motivated by the rise of online media that join in one company carrying the concept of collaborative economy. The focus of the problems analyzed is the process of selecting issues, choosing sources and word selection in news production by journalists, communicative events in the newsroom to the editorial gatekeeping process. The research method used is qualitative research, with ethnographic methods newsroom. Researchers used Shoemaker & Reese's hierarchy of influence theory to find out what influences media content as a result of routines in the newsroom. Determination of informants using purposive sampling techniques. The results obtained that the routine of journalists in producing content is influenced by the level of individuals and media routines. But the most influential factors are at the organizational level. Because it is related to the company's policy to produce content that can generate a lot of good profits for the Serangnews editorial team.mind-people journalists and Kabarbanten.pikiran.rakyat.com as well as for PRMN as the parent company. Keywords: Mass Communication, Online Media, PRMN, news Attack, News banten.